Perspectives on access to higher education : practice and research - Broadhead, Samantha; Davies, Rosemarie; Hudson, Anthony (Bingley, U.K. : Emerald Publishing Limited, 2019)
Access education has been through many changes since its beginnings in the late 1960s. Recent shifts in the academic landscape including standardization, grading, and new tensions in higher education raise difficult questions for educators regarding the future of access education.This book critically examines various aspects of Access education from a historical perspective. It proposes that there are particular 'Access' values that are shared by practitioners that can be at odds with the needs of higher education. Wider questions concerning funding and accountability underpinned by neoliberalism have also had an impact on Access education. The authors, practitioners and researchers of Access education, gather their insights in this timely book, grounded in authentic experience. They explore the ways in which policies and procedures have been developed in light of these tensions. By drawing particular attention to the voices of Access practitioners and highlighting the current constraints around curriculum design this book will prove invaluable for leaders, administrators, researchers and practitioners in further and higher education.
Prelims -- Introduction -- Access to higher education: from margin to mainstream -- Access to higher education: monitoring and standardisation -- Learning on a bespoke access programme -- The trust between access to higher education students and their tutors: a practitioner research project -- Accessing postgraduate education -- Conclusions -- Index.
Includes index.
Keywords: Universities and colleges -- Admission; College attendance; Educational equalization; Minorities -- Education (Higher); Education -- Higher; Higher & further education, tertiary education